First Comparative Analysis of Clostridium septicum Genomes Provides Insights Into the Taxonomy, Species Genetic Diversity, and Virulence Related to Gas Gangrene - Thomas, Prasad; Abdel-Glil, Mostafa Y.; Subbaiyan, Anbazhagan; Busch, Anne; Eichhorn, Inga; Wieler, Lothar H.; Neubauer, Heinrich; Pletz, Mathias; Seyboldt, Christian (Frontiers in Microbiology, 2021)
Clostridium septicum is a Gram-positive, toxin-producing and spore-forming bacterium that is recognized, together with C. perfringens, as the most important etiologic agent of progressive gas gangrene. C. septicum infections are almost always fatal in humans and animals. Despite its clinical and agricultural relevance, there is currently limited knowledge of the diversity and genome structure of C. septicum. This study presents the complete genome sequence of C. septicum DSM 7534T type strain as well as the first comparative analysis of five C. septicum genomes. The taxonomy of C. septicum, as revealed by 16S rRNA analysis as well as by genomic wide indices such as protein-based phylogeny, average nucleotide identity, and digital DNA-DNA hybridization indicates a stable clade. The composition and presence of prophages, CRISPR elements and accessory genetic material was variable in the investigated genomes. This is in contrast to the limited genetic variability described for the phylogenetically and phenotypically related species Clostridium chauvoei. The restriction-modification (RM) systems between two C. septicum genomes were heterogeneous for the RM types they encoded. C. septicum has an open pangenome with 2,311 genes representing the core genes and 1,429 accessory genes. The core genome SNP divergence between genome pairs varied up to 4,886 pairwise SNPs. A vast arsenal of potential virulence genes was detected in the genomes studied. Sequence analysis of these genes revealed that sialidase, hemolysin and collagenase genes are conserved compared to the α-toxin and hyaluronidase genes. In addition, a conserved gene found in all C. septicum genomes was predicted to encode a leucocidin homolog (beta-channel forming cytolysin) similar (71.10% protein identity) to Clostridium chauvoei toxin A (CctA) which is a potent toxin. In conclusion, our results provide first, valuable insights into strain relatedness and genomic plasticity of C. septicum and contribute to our understanding of the virulence mechanisms of this important human and animal pathogen.